SQUEEZE CEMENTING OPERATION TO CONTROL WATER PRODUCTION ON WELL OKTA-36 OF FIELD OKTA, EAST JAVA - Aldo Fadhillah Abraham; Rachmat Sudibjo; Andry Prima (Lembaga Penelitian Universitas Trisakti, 2015)
This thesis mainly discuss about workover (Squeeze Cementing) evaluation Activity in OKTA-36 well of OKTA field, East Java. The choice to did a workover activity in this well was because the oil and gas production for this particular carbonate well has been depleted. The cause of this problem was the watering problem near wellbore as the problem was found by using the Chan’s Diagnostics. Chan’s diagnostics is one of a method to determine the watering problem by comparing days to the existing production data. To increase the oil and gas productivity of this well, the justification was to close the old perforation interval of 6300ft – 6330ft MD by squeezing cement activity and then move the perforation interval to 6195ft – 6205ft MD and 6220ft – 6230ft MD. To fix the wellbore problem caused by water, the interval of 6260ft – 6262ft MD was also squeezed. The choice of 6260ft -6262ft MD was based on the tightness of the formation because of the total loss characteristics of the well. The result shows that the workover activity was a success because of the massive increase in oil and gas productivity. The numbers for the production performance analysis after workover activities are the WHP of 925 psi, WHT of 122o F, FLP 280 psi, Choke 30/64”, oil production 1242 BOPD, Water Cut 0% and Gas Production 0.950 MMSCFD